Memahami Pola Pendidikan Islam dan Hubungan Sosial Masyarakat dalam Model Universitas Pesantren di Ponorogo Jawa Timur - Aprilia Restuning Tunggal (Prodi Sosiologi FISIP Universitas Teuku Umar, 2023)
The assessment from various circles of society towards pesantren education is less objective, making the position of pesantren often in a disadvantaged position. Pesantren is considered very closed, far from society and exclusive. In fact, pesantren is an educational institution that is consistent in teaching social values and Islamic scholarship. This study aims to pay attention to the public's view of pesantren, which so far sees pesantren only with one side Then this study will describe the social relationship between the Islamic boarding school and the community and the form of social interaction between the Islamic boarding school and the community in the surrounding environment. While the method in this study is a qualitative method, data collection is done by literature review, field observations, and documentation. This study resulted in the findings that Islamic education contained in Islamic boarding schools can be well received by the community and is in line with social values that exist in society. Social relations between UNIDA Gontor and the community can be implememted by several activities, organizing, or grouping, even though there is a dividing wall. This is because individuals or humans always need social interaction and exchange.